Demonstrating a Framework for Rapid Development of Physically Situated Interactive Systems - Andrist, Sean; Bohus, Dan; Feniello, Ashley (14th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2019)
We demonstrate an open, extensible framework for enabling faster development and study of physically situated interactive systems. The framework provides a programming model for parallel coordinated computation centered on temporal streams of data, a set of tools for data visualization and processing, and an open ecosystem of components. The demonstration showcases an interaction toolkit of components for systems that interact with people via natural language in the open world.